Studies on Schismatoglottideae (Araceae) of Borneo XXIV — Two new species of Aridarum from Kalimantan, and notes on the Aridarum Burttii Complex - Wong, Sin Yeng; Boyce, P.C; Low, Shook Ling (BGBM Berlin-Dahlem., 2012)
Two taxonomically novel Aridarum species, A. kazuyae and A. orientale, are described from Kalimantan Timur, Indonesian Borneo. They are most similar to A. burttii from Sarawak, and together with A. minimum from Kalimantan Barat represent a morphotaxon, here called the Burttii Complex, defined by staminate flowers comprised of one stamen with an obliquely excavated expanded connective, hemispherical interstice staminodes, a spathe limb deliquescing acroscopically from its junction with the lower persistent portion and leaf blades with adaxially prominently raised primary lateral veins. Recognition of the new species proposed here takes the genus Aridarum to 12 accepted species. A key to all Aridarum species is provided, the two new species are illustrated and a comparison plate of the spadices of the four species assigned to the Burttii Complex as well as notes on the defining morphological features of this species group and some brief observations on pollination are given.